Efectos de la temperatura y la humedad sobre la emisión de CO2 y parámetros productivos en incubación artesanal - Murillo Reyes, Diego Fernando (2025)
The objective of this research was to evaluate the effect of different temperature and humidity levels on CO₂ emission and incubation parameters of fertile COBB 500 eggs in an artisanal incubation system. A total of 1,500 fertile eggs, weighing between 59 and 61 g, were randomly assigned to three treatments with five replicates of 100 eggs each: T1 (temperature 37°C, humidity 40%), T2 (temperature 37.5°C, humidity 50%), and T3 (temperature 38°C, humidity 60%), distributed under a Completely Randomized Design. The variables measured included CO₂ emission (ppm), discarded eggs during candling (%), and hatchability (%). The results indicate that T3 exhibited the highest CO₂ levels in the morning (3758 ppm), afternoon (4515 ppm), and night (3649 ppm), with a daily average of 3938 ppm, showing significant differences (p<0.01), highlighting the impact of temperature and humidity on CO₂ emission during incubation. Regarding candling, T3 presented the highest percentage of fertile eggs (92±1.58) and the lowest percentage of discarded eggs (8±1.58), with significant differences (p<0.01). Additionally, T3 showed the best results in live chick hatch rate (77.60±3.05) and hatchability percentage (84.35±3.27), with highly significant differences (p>0.01). In conclusion, temperature and humidity significantly affect CO₂ emission and incubation parameters of fertile COBB 500 eggs in an artificial incubation system.